2017
DOI: 10.1111/eci.12846
|View full text |Cite
|
Sign up to set email alerts
|

Combining echo and natriuretic peptides to guide heart failure care in the outpatient setting: A position paper

Abstract: Background: Chronic heart failure (HF) is a relevant and growing public health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
(87 reference statements)
0
7
0
1
Order By: Relevance
“…34 Thus, a position paper has recommended the use of BNP and LVFP in the management of HF patients in the ambulatory setting. 35 NT-proBNP also correlated strongly with indices of LVFP in a study of sixty-eight symptomatic patients with isolated diastolic dysfunction. 36 We also had a similar nding of positive correlation.…”
Section: Discussionmentioning
confidence: 86%
“…34 Thus, a position paper has recommended the use of BNP and LVFP in the management of HF patients in the ambulatory setting. 35 NT-proBNP also correlated strongly with indices of LVFP in a study of sixty-eight symptomatic patients with isolated diastolic dysfunction. 36 We also had a similar nding of positive correlation.…”
Section: Discussionmentioning
confidence: 86%
“…In the last years, LUS has been proposed for the evaluation of pulmonary congestion, through the assessment of B-lines. Quantification of B-lines has been shown to be useful for the diagnosis, monitoring, and risk stratification of patients with known or suspected acute HF [ 27 ] and may add to the assessment of hemodynamic congestion by echo Doppler parameters and NPs also in an outpatient setting [ 12 , 28 ]. The echo Doppler estimation of LVFP by E / e ′ and NPs is somewhat correlated with pulmonary tissue water in large populations, but may provide different information in the single patient [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining lung ultrasound (LUS) assessment of B-lines with EDT and E / e ′ may increase the diagnostic accuracy in estimating LVFP and in identifying pulmonary congestion [ 10 ]. Therefore, the combination of Doppler echocardiographic markers of LVFP, LUS, and NPs may be potentially valuable in guiding ambulatory HF management, since they can be useful in distinguishing stable patients from those at high risk of decompensation, optimizing treatment, reducing hospitalization, and consequently improving prognosis [ 11 , 12 ]. To investigate this concept, we compared the outcome of ambulatory patients with chronic HF and reduced or mildly reduced LV ejection fraction (EF) divided according to follow-up strategies: echo Doppler signs of elevated LVFP, LUS, and B-type natriuretic peptide (BNP)-directed follow-up (Group I); symptom-guided follow-up (Group II); and no organized follow-up for cardiovascular care (Group III).…”
Section: Introductionmentioning
confidence: 99%
“…There is serious concern about the strict resemblance of NP predictive values among patients with HFrEF/HFmrEF to those with HFpEF [37]. The DIAST-CHF trial revealed that NT-proBNP was a better predictor of incident atrial fibrillation than HF among stable outpatients with CV risk factors [38].…”
Section: Biomarkers Of Myocardial Stretch and Biomechanical Stressmentioning
confidence: 99%